Effective Ways to Maintain the Physical Performance of Students during Distance Learning - Oleksandr Mozolev (Pedagogical Discourse, 2022)
The objective of the research was to test the effectiveness of the fitness program «WAY TO A HEALTHY LIFE». Indicators of morphofunctional and physical condition of students during quarantine restrictions were studied. The total number of respondents was 926 students (474 girls and 452 boys) from four higher education institutions in Ukraine. To implement the fitness program, the authors developed a model of physical education of students for the period of distance learning. To obtain the necessary information, we used general scientific research methods, namely: analysis of scientific and methodological sources, pedagogical modeling, pedagogical experiment, pedagogical observation, research methods of functional and physical condition of students, expert evaluation method, mathematical statistics methods, SWOT analysis. Five tests characterizing morphofunctional indicators were selected by the method of expert assessment (Stange test; Genchi test; body mass index; Ruffier-Dickson’s index; Harvard step test) and seven tests that characterize the indicators of physical development of students (exercises for arm strength; exercise for dexterity, exercise for speed; exercise for the development of abs; exercise for endurance, standing long-jump, Burpie’s test). The experimental research showed that out of five tests that characterize the level of development of morphofunctional signs of the body’s activity, the girls had improvement in four and the boys in three indicators. Other morphofunctional indicators remained at the previous level. Of the seven tests that characterize the level of development of different physical qualities, significant positive changes were observed in the performance of four exercises in girls and two exercises in boys, maintenance of the level of physical development occurred in the performance of two exercises in girls and four exercises in boys. Only the performance of endurance exercises in girls and boys showed negative dynamics. The SWOT-analysis showed the effectiveness of using the fitness program «WAY TO A HEALTHY LIFE» during distance learning.